Quality of service in textile industry: evaluation of customers retailers - Santos, Leomar dos (2012)
This study aims to analyze the perception of the retail customers of a textile industry about the quality of services. Some studies have investigated the perception of quality of textile products, but are still incipient the studies that analyze the perceived quality of services provided by these companies. Researches of this nature become important because, besides of producing and marketing products, the textile industries also operate in providing various services to its customers, even those integrated in the sale of household products. The quality of these services can make a difference on how these companies obtain the satisfaction of its customers, adding value to products. We conducted a survey with the application of a structured questionnaire based on SERVQUAL model, on 130 retail customers of a textile company. For data analysis, descriptive statistics was used to identify the gaps in the analysis of this model. The SERVQUAL model has identified the major gaps between expectation and perception of quality, which can assist the company in defining priorities and actions for improvement. In this sense, are presented some managerial implications for the company studied. This study also intends to help the organization on implementing explicit criteria of quality in service delivery.